Bovine embryo survival under oxidative‐stress conditions is associated with activity of the NRF2‐mediated oxidative‐stress‐response pathway. Issue 6 (21st March 2014) - Amin, Ahmed; Gad, Ahmed; Salilew‐Wondim, Dessie; Prastowo, Sigit; Held, Eva; Hoelker, Michael; Rings, Franca; Tholen, Ernst; Neuhoff, Christiane; Looft, Christian; Schellander, Karl; Tesfaye, Dawit
SUMMARY In present study, we sought to examine the ability of preimplantation bovine embryos to activate the NF‐E2‐related factor 2 (NRF2)‐mediated oxidative‐stress response under an oxidative stress environment. In vitro 2‐, 4‐, 8‐, 16‐cell‐, and blastocyst‐stage embryos were cultured under low (5%) or high (20%) oxygen levels. The expression of NRF2, KEAP1 (NRF2 inhibitor), antioxidants downstream of NRF2, and genes associated with embryo metabolism were analyzed between the embryo groups using real‐time quantitative PCR. NRF2 and KEAP1 protein abundance, mitochondrial activity, and accumulation of reactive oxygen species (ROS) were also investigated in blastocysts of varying competence that were derived from high‐ or low‐oxygen levels. The expression levels of NRF2 and its downstream antioxidant genes were higher in 8‐cell, 16‐cell, and blastocyst stages under high oxygen tension, whereas KEAP1 expression was down‐regulated under the same conditions. Higher expression of NRF2 and lower ROS levels were detected in early (competent) blastocysts compared to their late (noncompetent) counterparts in both oxygen‐tension groups. Similarly, higher levels of active nuclear NRF2 protein were detected in competent blastocysts compared to their noncompetent counterparts. Thus, the survival and developmental competence of embryos cultured under oxidative stress are associated with activity of the NRF2‐mediated oxidative stress response pathway during bovine pre‐implantation embryo development. Mol. Reprod. Dev. 81: 497–513, 2014. © 2014 Wiley Periodicals, Inc.